Dynamic Corridor Illusion in Pigeons: Humanlike Pictorial Cue Precedence Over Motion Parallax Cue in Size Perception. (March 2020) - Hataji, Yuya; Kuroshima, Hika; Fujita, Kazuo
Depth information is necessary for perceiving the real size of objects at varying visual distances. To investigate to what extent this size constancy present in another vertebrate class, we addressed the two questions using pigeons: (a) whether pigeons see a corridor illusion based on size constancy and (b) whether pigeons prioritize pictorial cues over motion parallax cues for size constancy, like humans. We trained pigeons to classify target sizes on a corridor. In addition, we presented a dynamic version of corridor illusion in which the target and corridor moved side by side. Target speed was changed to manipulate motion parallax. With the static corridor, pigeons overestimated the target size when it was located higher, indicating that pigeons see a corridor illusion like humans. With the dynamic corridor, the pigeons overestimated the target size depending on target position, as in the static condition, but target speed did not affect their responses, indicating that the pictorial precedence also applies to pigeons. In a follow-up experiment using the same stimulus, we confirmed that humans perceive object size based on pictorial cues. These results suggest that size constancy characteristics are highly similar between pigeons and humans, despite the differences in their phylogeny and neural systems.